The postoperative monitoring of nonfunctioning pituitary adenomas - Wass, J; Reddy, R; Karavitaki, N (2011)
Clinically nonfunctioning pituitary tumors are common in tertiary endocrine practice. Although it is widely accepted that patients with these adenomas require long-term surveillance after surgery-particularly those with macroadenomas, which grow much more frequently than microadenomas-a consensus on postoperative monitoring and treatment strategies is lacking. The indications for radiotherapy, which has seen a decline in use over the past decade, are not clear, although most experts would agree that residual tumor mass after surgery, as well as tumor expansion into the cavernous sinus, indicate the need to consider postoperative radiotherapy. In patients not treated with radiotherapy after surgical treatment of a nonfunctioning adenoma, MRI of the tumor should be performed annually for the first 6 years and every 2 years thereafter. In addition, silent adrenocorticotropic hormone-secreting tumors can behave more aggressively if they recur, and tumor regrowth can also occasionally be found in patients after classical pituitary apoplexy, which suggests that individuals with these conditions should also be monitored carefully after surgery. However, at which point this scanning routine can be ceased remains the subject of debate, as few data on late recurrence of nonfunctioning pituitary adenomas exist. © 2011 Macmillan Publishers Limited. All rights reserved.